2021
DOI: 10.1042/bsr20210617
|View full text |Cite
|
Sign up to set email alerts
|

Integrated bioinformatics analysis reveals novel key biomarkers and potential candidate small molecule drugs in gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) is the metabolic disorder that appears during pregnancy. The current investigation aimed to identify central differentially expressed genes (DEGs) in GDM. The transcription profiling by array data (E-MTAB-6418) was obtained from the ArrayExpress database. The DEGs between GDM samples and non-GDM samples were analyzed. Functional enrichment analysis were performed using ToppGene. Then we constructed the protein–protein interaction (PPI) network of DEGs by the Search Tool for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 198 publications
0
10
0
Order By: Relevance
“…Moreover, PE‐significantly regulated proteins only in the PE group were mainly enriched in the ribosome and fatty acid metabolism pathways. Some studies suggested dysregulation of ribosomal pathways in PE [24, 25]. Transcriptional profiling of the decidua in PE revealed fatty acid metabolism might play an essential role in pathogenesis [26, 27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, PE‐significantly regulated proteins only in the PE group were mainly enriched in the ribosome and fatty acid metabolism pathways. Some studies suggested dysregulation of ribosomal pathways in PE [24, 25]. Transcriptional profiling of the decidua in PE revealed fatty acid metabolism might play an essential role in pathogenesis [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Alur et al. [24] revealed that HSP90AA1 were up‐regulated differentially expressed genes and were associated with GDM. And we also identified that the acetylation level of K209 on HSP90AA1 was increased in the GDM placentas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through diverse in silico tools analyzing the interaction of gene/protein/miRNA/transcription factors, they described an important dysregulation of certain placental hormones, including leptin, insulin/IGF-I and their receptors, and the placental growth hormone receptor. Recently, other hormonal candidates that might play a role in the pathophysiology of GDM have been described through comprehensive bioinformatics, gene analysis, ROC analysis, and RT-PCR, including β-hCG, oxytocin receptors, binding proteins of IGF-I, and some cytochromes involved in the steroidogenic pathway [34,35].…”
Section: Role Of Placenta In the Endocrine Milieu Of Gdmmentioning
confidence: 99%
“…During early gestation, the production of insulin is enhanced, while insulin sensitivity may or may not show any changes. However, during the later stages of pregnancy, female adipose tissue depots decline, whereas levels of post-prandial free fatty acids (FFAs) increase, and compared with pre-pregnancy, the glucose disposal mediated by insulin worsens by about 40-60% [19,27,34].…”
Section: Introductionmentioning
confidence: 99%